Management Experiences of the Business Operations of the Lafaayette Luxury Suites Resort (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
IntroductionContemporary beach resorts are undoubtedly well-acquainted with the intricate workings of the industry, where the cornerstone of business prosperity lies in ensuring customer satisfaction.  The guests in these establishments are typically discerning consumers who seek goods and services tailored to their desires and necessities.  Against this backdrop, the study explored the unique experiences of proprietors within the tourism sector, specifically focusing on those affiliated with the esteemed Lafayette Luxury Suites Resort.  This research was intrinsically geared towards addressing a fundamental inquiry: "What are the predominant narratives encapsulating the journey of the Lafayette Luxury Suites Resort throughout the challenging terrain of the COVID-19 pandemic?" MethodThe preparatory phase, preceding the commencement of data collection in December 2021, involved the judicious selection of a managerial participant through the meticulous application of criterion sampling.  The ethical clearance from the Ethics Review Board further underscored the rigor and integrity underpinning this study's methodologies.  Employing the Creswell phenomenology research design, the study penetrated the labyrinthine landscape of the chosen participant's experiences, elucidating the nuanced dimensions of management values that found expression within these narratives.  The inquiry the participant so responsibly and meticulously responded to be the axis upon which this research revolved. Results and DiscussionIn the execution of the research, data collection and analysis unfolded in tandem, orchestrated using the Creswell method of interpretation.  The findings crystallized into a triad of overarching themes, each encapsulating a pivotal facet of the participant's narrative journey:Navigating Uncertainty: The first theme, aptly titled "Thorn between the Line," thrust into the spotlight the formidable dilemmas business owners confront during the tumultuous pandemic.  The heart-wrenching decisions concerning the retention or severance of employee services served as a poignant embodiment of the challenges encountered. Adapting and Overcoming: The second theme, "Silver Lining," illuminated the remarkable resolve both business proprietors and their employees exhibited in recalibrating work arrangements.  This adaptive response aimed not only at ensuring a steady source of income for employees but also at safeguarding the operational vitality of the business amidst the pandemic's tempestuous winds. Exploring New Horizons: The third theme, aptly named "Opportunities," unveiled the unexpected tendrils of innovation that emerged amid the pandemic-induced adversity.  This facet illuminated the latent potential for diversification and expansion that had been hitherto unexplored, showcasing the adaptive capacity of the industry even in the face of unprecedented challenges. ConclusionGiven the profundity of the insights gleaned, a comprehensive inquiry into the study is advocated, urging a more profound understanding of the complexities at play.  Furthermore, the findings of this investigation can be wielded as a potent tool for designing and deploying market research, strategically aligning business endeavors with the dynamic demands of contemporary markets, and harnessing strategies that resonate deeply with local clientele. In essence, this study enriches the corpus of knowledge within the realm of hospitality and tourism and extends its implications as a foundational steppingstone for prospective research endeavors.  The multifaceted tales elucidated within this study not only provide fresh perspectives but also lay a robust groundwork for the cultivation of future studies that traverse the uncharted terrain of this domain.
Keywords: Management Experiences; services; changes; strategies